Efficient transgenesis and annotated genome sequence of the regenerative flatworm model Macrostomum lignano - Wudarski, Jakub; Simanov, Daniil; Ustyantsev, Kirill; De Mulder, Katrien; Grelling, Margriet; Grudniewska, Magda; Beltman, Frank; Glazenburg, Lisa; Demircan, Turan; Wunderer, Julia; Qi, Weihong; Vizoso, Dita B.; et al. (Nature Publishing Group, 2017)
Regeneration-capable flatworms are informative research models to study the mechanisms of stem cell regulation, regeneration, and tissue patterning. However, the lack of transgenesis methods considerably hampers their wider use. Here we report development of a transgenesis method for Macrostomum lignano, a basal flatworm with excellent regeneration capacity. We demonstrate that microinjection of DNA constructs into fertilized one-cell stage eggs, followed by a low dose of irradiation, frequently results in random integration of the transgene in the genome and its stable transmission through the germline. To facilitate selection of promoter regions for transgenic reporters, we assembled and annotated the M. lignano genome, including genome-wide mapping of transcription start regions, and show its utility by generating multiple stable transgenic lines expressing fluorescent proteins under several tissue-specific promoters. The reported transgenesis method and annotated genome sequence will permit sophisticated genetic studies on stem cells and regeneration using M. lignano as a model organism.
WOS: 000417906400004
PubMed ID: 29242515
Keywords: Efficient Transgenesis; Annotated Genome Sequence; Regenerative Flatworm Model; Macrostomum Lignano